Aspek Perancangan Generator Magnet Permanen Fluks Aksial 1 Fasa Untuk Mengakomodir Kecepatan Putar 500-600 RPM - Azmi Alfarisi; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
A permanent magnet generator is designed to accomodate wind speed of 7-12 m/s, which is equal to 500-600 RPM. It is consider as a low speed generator. This generator is dedicated for Wind Power Plant (PLTB) system. Parameters which are influence to the permanent magnet generator performance is described. Finally some strategies to achieve optimized value for those parameters will be elaborated from software magnet design perspective.Keyword : Permanent magnet generator, low speed, PLTB